The diagnostic value of apparent diffusion coefficient to differentiate benign and malignant meningiomas - Marissa, Risa; Rahayu, Rachmi Fauziah; Wujoso, Hari; Subandi, Subandi; Putro, Prasetyo Sarwono; Soewondo, Widiastuti (Universa Medicina, 2021)
BACKGROUNDMeningiomas are the most common primary extra-axial non-glial intracranial tumors. The severe grade of meningioma, according to WHO, has the highest recurrence rate accompanied by high morbidity and mortality rates. Therefore, it is imperative to perform pre-operative assessments so the clinician can give prompt treatment to gain a better prognosis. It is a novel alternative way of predicting meningioma’s malignancy by calculating the tumor’s apparent diffusion coefficient (ADC) value. The objective of the study was to determine the value of ADC for differentiating benign and malignant meningiomas. METHODSThis cross-sectional study involved 32 subjects with clinically diagnosed or histologically verified meningioma (21 benign and 11 malignant). They underwent a head-magnetic resonance imaging (MRI) examination and biopsy. We calculated the ADC value by creating regions of interest (ROIs) on the solid part of the tumor, guided by contrast and fluid-attenuated inversion recovery (FLAIR) sequence. We analyzed the ADC value with independent t-test and Bland-Altman graphs, calculated the average difference, CI 95%, limit of agreement between observers, and ROC. RESULTSMean ADC of malignant meningiomas (0.877 ± 0.167 x 10-3 mm2/s) was significantly lower than that of benign meningiomas (0.990 ± 0.105 x 10-3 mm2/s) (p<0.05). The ADC threshold is 0.886 x 10-3 mm2/s with sensitivity 63.6%, specificity 85.7%, positive predictive value 70% and negative predictive value 81.8%. CONCLUSIONThe ADC value measurement provides a discriminative feature to differentiate between benign and malignant meningiomas. However, the clinical applicability still needs to be elucidated, as histopathological confirmation remains the mainstay of definitive diagnosis.